Income Diversification Strategy on Bank Stability:International Banks Evidence - Handy Octavianus; Khaira Amalia Fachrudin (University of Merdeka Malang, 2022)
This study aims to analyze the implementation of the income diversification strategy on bank stability carried out by international banks. This study uses panel data from 32 international banking companies from 2010-2019 with a total of 320 firm years of observation. The generalized method of moments is used as a statistical analysis tool for panel data. The study results show that the implementation of the income diversification strategy carried out by international banks was convincingly able to increase bank stability. This indicates that international banks were able to perform cost diversification efficiency to achieve better stability. Furthermore, the use of high leverage could reduce bank stability. This study shows robust results in the measurement of income diversification using either the Herfindahl Hirschman Index (HHI) or the ratio of non-interest income to total income. This is a premier formal assessment of the nexus between income diversification strategies and risk management among the largest commercial banks in the world context. This research is expected to be useful for banking management, regulators, and investors in the banking sector.